An improved rheology model for the description of the rate-dependent cyclic behavior of high damping rubber bearings. Issue 77 (October 2015) - Nguyen, D.A.; Dang, J.; Okui, Y.; Amin, A.F.M.S.; Okada, S.; Imai, T.
Abstract: An improved rheology model, inspired from explicit experiments is conceived to represent rate-dependent cyclic shear behavior of high damping rubber bearings at subzero and room temperatures. Total stress has been decomposed into nonlinear rate independent elasto-plastic stress, nonlinear elastic stress and nonlinear visco-elasto-plastic overstress branches. To represent nonlinear viscosity behavior, 'overstress branch' has been generalized by putting linear elastic spring in parallel to nonlinear elasto-plastic model, placed in series with nonlinear dashpot. Constitutive relations for model elements have been designated for respective fundamental phenomenon observed in constant strain rate experiments. An optimum calculation approach is developed to determine a unique set of overstress parameters capable not only of representing constant strain rate cyclic tests but also sinusoidal tests with variable input strain rates. Essential abilities of the proposed model and adequacy of estimated parameters have been confirmed by comparing numerical simulation results with experiments conducted at −30 °C, −10 °C and 23 °C. Highlights: ● Rate-dependent behavior of high damping rubber bearing (HRDB) at low temperature. ● Experiments on scaled bearings to compare behaviors at room and low temperatures. ● An improved rheology model of HDRB for seismic analysis. ● Visco-elastoplastic effects are generalized for room and low temperature behaviors. ● Single parameter set for simulating constant and variable input strain rate tests.